From Conflict to Compromise: Experimental Evidence on Occupational Downgrading in Migration from Myanmar - Yashodhan Ghorpade; Muhammad Saad Imtiaz (Institute of Labor Economics (IZA), 2025)
We examine the relationship between violent conflict and the willingness of potential migrants to accept lower skilled work (occupational downgrading). We develop a theoretical model of migration decisions, which we test using an innovative survey module administered to high-skilled youth in Myanmar. Consistent with the predictions of the model, we show that insecurity induced by conflict reduces the additional wage premium that individuals would typically demand for taking on lower-skilled work, indicating greater amenability to occupational downgrading. These effects are particularly pronounced for disadvantaged groups, such as women, ethnic minorities, and those with weaker labor market networks or English language skills. The results are driven by respondents from areas under territorial contestation, and those interviewed after the sudden activation of a conscription law during the survey. This further confirms how security considerations may override the preference for skill-appropriate job matching, suggesting that conflict may worsen labor market outcomes and reduce potential gains from migration, especially for disadvantaged groups.
Keywords: J61; O15; F22; 330; occupational downgrading; migration; conflict; compensating differential; Myanmar